Peer review of the pesticide risk assessment of the active substance lavandulyl senecioate. (13th March 2020) - ,; Abdourahime, Himdata; Anastassiadou, Maria; Arena, Maria; Auteri, Domenica; Barmaz, Stefania; Brancato, Alba; Brocca, Daniela; Bura, Laszlo; Carrasco Cabrera, Luis; Chiusolo, Arianna; Civitella, Consuelo; et al.
Abstract : The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessments carried out by the competent authority of the rapporteur Member State Italy for the pesticide active substance lavandulyl senecioate are reported. The context of the peer review was that required by Regulation (EC) No 1107/2009 of the European Parliament and of the Council. The conclusions were reached on the basis of the evaluation of the representative use of lavandulyl senecioate a pheromone comprise manual applications to control Planococcus ficus (vine mealybug) populations by mating disruption in table grape, wine grape, raisins and any other crops where P. ficus may be a pest in Southern Europe. The reliable endpoints, appropriate for use in regulatory risk assessment are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.